PENERAPAN BUDAYA MUTU AKADEMIK DALAM PENINGKATAN KUALITAS PENULISAN SKRIPSI - Jasper Simanjuntak; Peny Husna Handayani; Nasriah Nasriah; Salim Salim (JURNAL TEMATIK, 2018)
The purpose of this research is to implement an academic culture and to determine the improvement of the thesis writing quality of PG PAUD students through the application of academic culture. This research was conducted in department of PG-PAUD. The sample in this study were PG PAUD students who were working on their thesis and thesis supervisor. This type of research is qualitative research with survey methods. The collect data through questionnaires, interviews, and observations. Based on the survey results, it can be concluded that the application of a culture of academic quality in improving the thesis in the PG-PAUD FIP UNIMED Study Program has been carried out by 91% of the thesis supervisors. The average application of the culture of academic quality in improving the thesis carried out by the thesis supervisor is in the very good category. The implementation of a culture of academic quality in improving the thesis in the PG-PAUD FIP UNIMED Study Program has been carried out by 83% or almost all of the thesis compilers. The average application of the culture of academic quality in improving the thesis carried out by thesis compilers is in the very good category. Aspects of thorough, rational, objective, honest, open, and productive have been applied by 100% or all students who compile the thesis